PENINGKATAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MATERI SISTEM GERAK MELALUI PENERAPAN MODEL PEMBELAJARAN MURDER (Mood, Understand, Recall, Digest, Expand, Review) - Yusmar Yusuf; Ningsi Saibi; Muhammad Riswan Ramli; Nursia Nursia (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2021)
Abstract: The research is Classroom Action Research which aims to improve the activity and results of student learning through applying the learning model of MURDER. The subject of this research is the grade XI IPA in one of SMA Negeri in Parepare, a total of 34 students. The implementation of this research consists of two cycles. The data was collected in the analysis using quantitative descriptive analysis. The data analysis results are as follows; (1) Student learning activities related to the implementation of the application of the model of learning in the form of MURDER such as students listening to an explanation of the learning materials increased from cycle I by the percentage of 88.2% to 91.1% in cycle II. Students' focus on learning increased from 27.4% to 58.8%. Students read certain material without remembering increased from 61.7% to 45.7%. Students give an oral presentation by repeating the material read increased from 45.7% to 79.4%. If it comes up, error-correcting students increased from 47% to 82.3%. Students elaborating material together couples increased from 50% to 58.8% and transmits the material on student other couples in the Group increased from 41.1% to 61.7%, (2) the results of the study of biology students after the application of the model of learning MURDER increased from cycle I with a percentage of 66.79 became 80.65 on cycle II. And the percentage of students who completed cycle I of 29.41 became 86.69 on cycle II. In brief, experience increased during the learning process after applying the learning model applied to MURDER. Keywords: Activity, Learning Outcomes, MURDER Model